Game meat as alternative food source for Africa: a retailer perspective - Slabbert, E., author; Saayman, M., author; van der Merwe, P., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The issue of food (in) security is critical in many parts of the world including Africa. Citizens have the right to sufficient food, water and social security which means sufficient provision of food on a day-to-day basis. South Africa has the largest privately owned wildlife industry in the world where game farmers utilise more or less 16.8% of South Africa's agricultural land (semi-arid which is best for wildlife farming) for wildlife related activities. This holds enormous potential for Africa in terms of food security. The effective and safe provision of game meat in South Africa and the export thereof can play an important role in contributing to food security. Qualitative research will be done through interviews with major distributors of game meat in South Africa to determine the magnitude of this industry from a supply perspective. Specific attention is given to distributors' perspective of consumer preferences in terms of species, the amount and types of game meat sold and the general consumption patterns of this market. The fact that the wildlife industry lacks data on the consumption of game meat in South Africa hampers the growth of this industry. This information will therefore contribute to growth but also inform stakeholders on the current status of this industry from a supply perspective.
Game meat as alternative food source for Africa: a distributer perspective
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.